2019
DOI: 10.1002/jsde.12266
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Concocting of Cross‐Linked Enzyme Aggregates of Candida antarctica Lipase B (Novozyme 435) for the Biomanufacturing of Rhamnolipids

Abstract: In the present study, Candida antarctica lipase B was immobilized on amine‐functionalized silica microspheres as cross‐linked enzyme aggregates (CLEA) and utilized for the biomanufacturing of rhamnolipids (RL). Lipase CLEA synthesized under optimized conditions of 2.0:1.0 by volume of silica microsphere/enzyme concentration, a 1.0:2.5 (v/v) ratio of enzyme/2‐propanol, 7 mM glutaraldehyde concentration, when incubated at pH 9.0 and 40 °C, for a cross‐linking time of 30 min were observed to exhibit superior bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Water molecules in trace amount are important in lipase‐mediated reaction, as it maintains the three‐dimensional structural integrity and the biocatalytic activity of the enzyme. However, an excess amount of water molecules is deleterious to the activity of lipases [21]. Hence, in order to draw a comparison between the synthesis of the two esters using free and covalently immobilised CaLB in aqueous and hexane systems, the equivalent amount of acid consumed for 20 h, with periodic estimation of percentage ester formation, was studied:C 2 H 4 O 2 + thickmathspaceC 2 H 5 normalOH false→ normalC H 3 normalCOOC H 2 normalC H 3 + thickmathspaceH 2 normalO thickmathspaceC 4 H 8 O 2 + C 2 H 5 normalOH false→ normalC H 3 normalC H 2 normalC H 2 normalCOOC H 2 normalC H 3 + thickmathspaceH 2 normalO thickmathspace The volume of the base used corresponded to an equivalent amount of acid in the reaction mixture, which is indicative of the amount of acid being used for ester synthesis, and pointed to the percentage ester formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Water molecules in trace amount are important in lipase‐mediated reaction, as it maintains the three‐dimensional structural integrity and the biocatalytic activity of the enzyme. However, an excess amount of water molecules is deleterious to the activity of lipases [21]. Hence, in order to draw a comparison between the synthesis of the two esters using free and covalently immobilised CaLB in aqueous and hexane systems, the equivalent amount of acid consumed for 20 h, with periodic estimation of percentage ester formation, was studied:C 2 H 4 O 2 + thickmathspaceC 2 H 5 normalOH false→ normalC H 3 normalCOOC H 2 normalC H 3 + thickmathspaceH 2 normalO thickmathspaceC 4 H 8 O 2 + C 2 H 5 normalOH false→ normalC H 3 normalC H 2 normalC H 2 normalCOOC H 2 normalC H 3 + thickmathspaceH 2 normalO thickmathspace The volume of the base used corresponded to an equivalent amount of acid in the reaction mixture, which is indicative of the amount of acid being used for ester synthesis, and pointed to the percentage ester formation.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction mixture was then incubated for 0.5–24 h, followed by washing three times to obtain the desired covalently bound CaLB. The activity of the free and immobilised CaLB was measured according to the procedure previously established by our group [21] and the absorbance was measured at 410 nm ( ɛ max 15,000 M −1 cm −1 ). One unit (U) of lipase activity was defined as the amount of enzyme needed to produce 1 μmol of pNP from pNPP at pH 8.0 and 40°C in 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reusability of immobilized inulinase (2.5 U/mg) was evaluated by performing repeated batch runs of inulin hydrolysis at 50°C and it was observed that 10 cycles of operation could be achieved with the immobilized inulinase. In the first cycle of inulin hydrolysis, the fructose release was 34 g/L, which gradually declined to 23.6 g/L at the fifth cycle, which could be due to the leaching out of the enzyme due to continuous washing [54]. Further, at the tenth cycle, the fructose released subsequently dropped to 9.2 g/ L, probably due to the decrease in thermal stability of the immobilized inulinase after prolonged incubation at 50°C [54] (Fig.…”
Section: Reusability Of Immobilized Biocatalyst/catalyst In Hmf Productionmentioning
confidence: 91%